Gram-Negative Bacterial Envelope Homeostasis under Oxidative and Nitrosative Stress - Thibault Chautrand; Djouhar Souak; Sylvie Chevalier; Cécile Duclairoir-Poc (Microorganisms, 2022)
Bacteria are frequently exposed to endogenous and exogenous reactive oxygen and nitrogen species which can damage various biomolecules such as DNA, lipids, and proteins. High concentrations of these molecules can induce oxidative and nitrosative stresses in the cell. Reactive oxygen and nitrogen species are notably used as a tool by prokaryotes and eukaryotes to eradicate concurrent species or to protect themselves against pathogens. The main example is mammalian macrophages that liberate high quantities of reactive species to kill internalized bacterial pathogens. As a result, resistance to these stresses is determinant for the survival of bacteria, both in the environment and in a host. The first bacterial component in contact with exogenous molecules is the envelope. In Gram-negative bacteria, this envelope is composed of two membranes and a layer of peptidoglycan lodged between them. Several mechanisms protecting against oxidative and nitrosative stresses are present in the envelope, highlighting the importance for the cell to deal with reactive species in this compartment. This review aims to provide a comprehensive view of the challenges posed by oxidative and nitrosative stresses to the Gram-negative bacterial envelope and the mechanisms put in place in this compartment to prevent and repair the damages they can cause.